A efetividade das decisões do Conselho Nacional de Saúde: mecanismos e agenda governamental - Santos, Allison Haley dos (2018)
The present dissertation proposes to verify if the decisions of the National Health Council are effective, considering the decision-making effectiveness as the fulfillment of the resolutions and the incorporation of the deliberate topics in the governmental agenda. It also had as an scope to analyze and describe the decision-making performance of the council, considering the resolutions produced in the period 2007 to 2017 and unravel the mechanisms that influence the process of building of the governmental agenda, taking as unit resolutions on public policies. The theoretical-analytical perspectives considered retake the research agendas on the effectiveness of participation / participatory institutions and adopts some elements of the descriptive models of the literature on the construction of the governmental agenda. The approach used was qualitative, being a case study, constituting an exploratory and descriptive research. As a data collection instrument, a semi-structured interview with key actors and indirect documentation was used. The analyzes of the data generated were based on the evidences extracted from the documents and interpretation of the interviews, using the technique of content analysis. The results showed that the national health council has a low performance in terms of producing resolutions with a potential incidence on public policies. Most resolutions on SUS funding have not been complied with by the government. The theme of healthy eating to combat obesity, deliberete by the council, was incorporated into the government agenda. The mechanisms used were the construction of an intersectoral articulated network, the cooperative mobilization between civil society entities and entrepreneurs of policies working in the bureaucracy, the restructuring of institutions, the insertion of thematic in the participatory spaces, as well as the political qualification of the technical staff and the use of the political force of other organs linked to the Presidency of the Republic. The variables used to analyze the institutional dimension revealed that the design of the National Health Council was essential for the use of mechanisms and defining the strategies used by enterpreuners of policies.